Brown gold : milestones of African-American children's picture books, 1845-2002 - Martin, Michelle H., 1966- (New York : Routledge, 2004)
Brown Gold is a compelling history and analysis of African-American children's picturebooks from the mid-nineteenth century to the present. At the turn of the nineteenth century, good children's books about black life were hard to find -- if, indeed, young black readers and their parents could even gain entry into the bookstores and libraries. But today, in the "Golden Age" of African-American children's picturebooks, one can find a wealth of titles ranging from Happy to be Nappy to Black is Brown is Tan. In this book, Michelle Martin explores how the genre has evolved from problematic early works such as Epaminondas that were rooted in minstrelsy and stereotype, through the civil rights movement, and onward to contemporary celebrations of blackness. She demonstrates the cultural importance of contemporary favorites through keen historical analysis -- scrutinizing the longevity and proliferation of the Coontown series and Ten Little Niggers books, for example -- that makes clear how few picturebooks existed in which black children could see themselves and their people positively represented even up until the 1960s. Martin also explores how children's authors and illustrators have addressed major issues in black life and history including racism, the civil rights movement, black feminism, major historical figures, religion, and slavery. Brown Gold adds new depth to the reader's understanding of African-American literature and culture, and illuminates how the round, dynamic characters in these children's novels, novellas, and picturebooks can put a face on the past, a face with which many contemporary readers can identify
"Hey, who's the kid with the green umbrella?" : a reevaluation of little Black sambo and the Black-a-moor -- From Ten little niggers to Afro-Bets : images of Blackness in picture books for young readers, 1870s to 2000s -- The influence of the Black arts movement on African American children's picture books -- Pushing the boundaries : the Coretta Scott King Award picture books -- From margin to center : African-American artistic legacies shaping the genre -- Historical America through the eyes of the Black child -- "Just build me a cabin the corner of glory land" : depictions of heaven in African-American children's picture books -- "Ain't I fine?" : Black modes of discourse in contemporary African American children's picture books -- "Why are we reading this stuff?" : a pedagogy of teaching African-American children's picture books
Includes bibliographical references (pages 211-221) and index
Print version record
eBooks on EBSCOhost
Keywords: American literature -- African American authors -- History and criticism; American literature -- African American authors -- Bibliography; Children's literature, American -- History and criticism; Children's literature, American -- Bibliography; Picture books for children -- United States -- Bibliography; Picture books for children -- United States; African Americans in literature; African Americans in art; Littérature de jeunesse américaine -- Histoire et critique; Littérature de jeunesse américaine -- Bibliographie; Livres d'images pour enfants -- États-Unis -- Bibliographie; Livres d'images pour enfants -- États-Unis.; Noirs américains dans la littérature.; Noirs américains dans l'art.; LITERARY CRITICISM -- American -- General; African Americans in art; African Americans in literature; American literature -- African American authors; Children's literature, American; Picture books for children; United States; Bibliographies; Criticism, interpretation, etc